KAJIAN FILOSOFIS TERHADAP STANDAR PERILAKU ETIS NOTARIS - Supriyanta, Supriyanta (Faculty of Law, Universitas Sebelas Maret, 2013)
A notary bound norms and values that constitute the parameters behave ethically. Philosophically, there is a size that is not universally applicable in the world of ethical behavior parameters notary. In a more concrete level, and factual measures for ethical behavior is a notary public Notary code of Ethics. In order to realize a notary ethical behavior, integrity and commitment required in the process of enforcement of the code Notary substance through a mechanism that has been agreed. This process must be done continuously so that woke standards of ethical behavior that can guide behavior that is not only derived from the text of the Notary Code, but also from a contextual understanding of the implementation of the Notary code of Ethics. Notary code of Ethics as the only parameter Notary ethical behavior in the sense that the most factual, should always be tailored to the developmental dynamics that occur in the community, so that the values contained in it maintained its existence.